2017
DOI: 10.18203/2349-2902.isj20175883
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of surgical jaundice: an institutional experience

Abstract: Background: Patients with surgical jaundice need quick and precise diagnosis for the presence of an obstruction in the biliary tract, to establish the level and nature of the lesion. The importance of history and clinical examination in arriving at a correct pre-operative diagnosis needs to be emphasized. Present study attempts to determine the various causes, age and sex pattern in extra hepatic obstructive jaundice.Methods: 100 patients with surgical jaundice were studied at IMS and SUM Hospital, Bhubaneswar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Malignant conditions are the most common aetiological cause [ 1 , 2 , 4 ] and palliative procedures are performed more frequently in this patient group due to late presentation [ 3 ]. Some studies have demonstrated a male predominance [ 5 , 6 ] while others have demonstrated a female predominance [ [2] , [3] , [4] , 7 , 8 ] in the gender distribution of this condition. We do not know if this is the same for our region and country.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant conditions are the most common aetiological cause [ 1 , 2 , 4 ] and palliative procedures are performed more frequently in this patient group due to late presentation [ 3 ]. Some studies have demonstrated a male predominance [ 5 , 6 ] while others have demonstrated a female predominance [ [2] , [3] , [4] , 7 , 8 ] in the gender distribution of this condition. We do not know if this is the same for our region and country.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis needs to be usually carried out through standard diagnostic processes like according to the history, biochemical test, physical examination and investigations. [5] Several diagnostic and therapeutic challenges have been faced by the general surgeon while managing the surgical jaundice and these challenges have been mostly sound while practicing in the countries with limited resources. [6,7]…”
Section: Introductionmentioning
confidence: 99%
“…It can present with acute symptoms or gradually progressive indolent course depending upon the underlying cause. 2 Percutaneous transhepatic biliary drainage (PTBD) is a minimally invasive procedure for drainage of the biliary system. 3 PTBD is preferred as the primary procedure in patients who have had prior bilio-enteric anastomosis, or those who are unsuitable for endoscopic retrograde cholangiopancreatography (ERCP) due to other reasons.…”
Section: Introductionmentioning
confidence: 99%